Status Judgment : New Insight into the Promoting Process of Entrepreneurial Behavior - حمود العنزي, سعد علي; علي, عامر حسين (Journal of Economics and Administrative Sciences, 2010)
The present study aims to explore determinants of entrepreneurial behavior from perspective of social theory. It is based on model notions of (Tyler & Blader, 2003) which have focused on studying role of positively personal and social identity in motivating employees to practicing desired behavior which serves the organization in which they work. Based on these notions and previous literature, study model were built. This model explains the relationship between status judgments (perceived internal respect and perceived external prestige)  and entrepreneurial behavior. It includes three main hypotheses. The first and second hypothesis are concerning the relationship between status judgments and entrepreneurial behavior while the third hypothesis pays attention to test role of perceived external prestige as moderator variable for relationship between perceived internal respect and entrepreneurial behavior. Data collected from sample included three colleges of AL-Qadisiyah university which is consisted (152) employees. After extraction findings, number of meaningful conclusions and recommendations were formulated.